2019
DOI: 10.1111/epi.16399
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefit of presurgical EEG‐fMRI in difficult‐to‐localize focal epilepsy: A single‐institution retrospective review

Abstract: Objective: The aim of this report is to present our clinical experience of electroencephalography-functional magnetic resonance imaging (EEG-fMRI) in localizing the epileptogenic focus, and to evaluate the clinical impact and challenges associated with the use of EEG-fMRI in pharmacoresistant focal epilepsy. Methods: We identified EEG-fMRI studies (n = 118) in people with focal epilepsy performed at our center from 2003 to 2018. Participants were referred from our Comprehensive Epilepsy Program in an explorato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 45 publications
3
40
0
Order By: Relevance
“…In agreement with a recent retrospective review investigating the clinical impact of EEG-fMRI in the presurgical setting (31), our results suggest that in patients with TLE short EEG-fMRI recordings are not useful for the surgical decision. When a clear epileptogenic lesion is detected on structural MRI, which matches the epileptogenic focus defined by the video-EEG data, EEG-fMRI might not add information for the surgical planning.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with a recent retrospective review investigating the clinical impact of EEG-fMRI in the presurgical setting (31), our results suggest that in patients with TLE short EEG-fMRI recordings are not useful for the surgical decision. When a clear epileptogenic lesion is detected on structural MRI, which matches the epileptogenic focus defined by the video-EEG data, EEG-fMRI might not add information for the surgical planning.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, IED were recorded in 75% of the patients and in 58% a BOLD signal change was observed. These results are in line with the previous EEG-fMRI studies, confirming that a major limitation for the use of the technique in the presurgical setting in TLE patients is the low numbers of IEDs recording during EEG-fMRI (10), and in particular, for mesial TLE, which often generates infrequent scalp-detectable IEDs (31).…”
Section: Discussionsupporting
confidence: 89%
“…Scalp EEG-fMRI studies have shown that IED-related BOLD changes in EZ can predict good postsurgical outcome (9,13,14,(22)(23)(24)(25)(47)(48)(49). One of the limiting factors for these studies has been low sensitivity of scalp EEG to capture the whole spectrum of epileptiform activity that can be revealed by invasive recordings (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…This can be difficult to accurately identify prior to surgery, yet better localization may improve surgical planning, and in turn improve outcomes. 1 Over the past 20 years, simultaneous scalp electroencephalographic (EEG)-functional magnetic resonance imaging (fMRI) has become a noninvasive tool to localize blood oxygen level-dependent (BOLD) responses to focal interictal epileptiform discharges (IEDs). [2][3][4] The overall pattern of BOLD signal changes has been suggested to reflect the network involved in the propagation of IEDs, 5 and the maximal BOLD cluster to indicate the area generating the IED, which has been termed "the spike onset zone."…”
Section: Introductionmentioning
confidence: 99%
“…For patients with drug‐resistant focal epilepsy undergoing evaluation for epilepsy surgery, it is critical to accurately localize the epileptogenic zone. This can be difficult to accurately identify prior to surgery, yet better localization may improve surgical planning, and in turn improve outcomes 1 . Over the past 20 years, simultaneous scalp electroencephalographic (EEG)–functional magnetic resonance imaging (fMRI) has become a noninvasive tool to localize blood oxygen level‐dependent (BOLD) responses to focal interictal epileptiform discharges (IEDs) 2–4 .…”
Section: Introductionmentioning
confidence: 99%